Analysis of Consumer Risk Perception on Online Auction Features - Reski Mai Candra; Noorminshah A. Iahad (Institute of Advanced Engineering and Science, 2013)
This study examines consumer’s perception related to perceived risk while doing transaction in e-auction system. Previous researches found there are some features in e-auction system recognized unclarity features as they indicate having fraud or cheating. In the online auction environment, perception could be categorized in two types such as privacy and security. This study proposed a conceptual framework based on perceived risks from consumer’s investigation, associated directly with four cost features of e-auction system: payment method, auction fee, bidding fee and third party services that combined with four perceived risk components: performance risk, psychological risk, financial risk, and time risk. Researcher has developed a questionnaire for collecting data from consumer’s who has experience in using e-auction. Through statistical analysis using multiple regressions, this study found that payment method, auction fee, and bidding fee have a positive impact on perceived risk. However, third party services have a significant effect upon consumer perceived risk on financial risk but not significant effect to time risk. Furthermore, the online auction features is directly related to reducing consumers' risk perception. As a summary, online auction features associated with financial play a crucial role in reducing consumers' perceived risk in online auction transactions.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.2529